Cold water immersion is acutely detrimental but increases performance post-12 h in rugby players - Garcia, C. A.; da Mota, G. R.; Marocolo, M. (International Journal of Sports Medicine, 2016)
We evaluated the effectiveness of cold water immersion on recovery of performance (i. e., the ability of repetitively performing a physical test) in rugby players acutely and 12 h later. 8 male rugby union players (23±4.7 years; 176.9±4.5 cm; 87.5±8.6 kg) performed a rugby-specific exercise protocol (40 min) followed by recovery strategies: cold water immersion (8.9±0.6°C; 9?min with 1 min out of water, repeated twice) or control (players remained seated for 20 min) in a random order. The players underwent performance tests (countermovement and 30 s continuous jumps and agility T) at 4 time points: at baseline, immediately after rugby-specific exercise, post-recovery strategies and 12 h later. The performance of the agility and countermovement jump test were not different between cold water immersion and control immediately post rugby-specific exercises and 12 h thereafter. However, the 30?s continuous jump test performance decreased immediately but increased 12 h later after cold water immersion compared with control. Perception of recovery was better in the cold water immersion group compared with controls post 12 h exercise. Cold water immersion improves 30?s continuous jump performance, total quality recovery and seems to be an easy and practical tool for coaches and players, especially during congested periods of the season when fast recovery (~12 h) for the following activity is essential.